2020
DOI: 10.3390/ijms21217890
|View full text |Cite
|
Sign up to set email alerts
|

Organic Cation Transporters in Human Physiology, Pharmacology, and Toxicology

Abstract: Individual cells and epithelia control the chemical exchange with the surrounding environment by the fine-tuned expression, localization, and function of an array of transmembrane proteins that dictate the selective permeability of the lipid bilayer to small molecules, as actual gatekeepers to the interface with the extracellular space. Among the variety of channels, transporters, and pumps that localize to cell membrane, organic cation transporters (OCTs) are considered to be extremely relevant in the transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 186 publications
(277 reference statements)
2
35
0
Order By: Relevance
“…4 d and Supplementary Table S1 ). Finally, due to the importance of glycosylation in neuroserpin polymerization in FENIB 23 , 25 , we exposed neuronal cultures to an alternative source of fully glycosylated neuroserpin by co-culturing the primary neurons with HEK-293 cells stably overexpressing and secreting either wild-type or G392E-mutant neuroserpin for 18 h. Again, no significant differences in density or area of synaptic puncta were observed (Fig. 4 d and Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…4 d and Supplementary Table S1 ). Finally, due to the importance of glycosylation in neuroserpin polymerization in FENIB 23 , 25 , we exposed neuronal cultures to an alternative source of fully glycosylated neuroserpin by co-culturing the primary neurons with HEK-293 cells stably overexpressing and secreting either wild-type or G392E-mutant neuroserpin for 18 h. Again, no significant differences in density or area of synaptic puncta were observed (Fig. 4 d and Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 97%
“…To address toxicity in post-mitotic neurons, we used primary, fully differentiated hippocampal neurons and treated them with recombinant G392E-mutant neuroserpin used at 20 nM, a concentration of the serpin shown before to be, in its wild-type form, well tolerated by primary hippocampal neurons and protective against oxidative stress 34 , or 100 nM. To address the possibility that glycosylation plays a role in the extracellular effects of neuroserpin, maybe through an increase in polymer formation as reported before 23 , 25 , we extended our analysis by co-culturing primary neurons with HEK-293 cells stably expressing wild-type or G392E-mutant neuroserpin. We used a density of HEK-293 cells that was well tolerated by neurons and similar to experiments where extracellular polymers were easily detectable.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple transporters have been reported for oxaliplatin, i.e., the organic cation transporter system (SLC22A), including OCT2 (SLC22A2) [13] and OCT3 (SLC22A3) [14], organic cation/carnitine transporters OCTNs (OCTN1/OCTN2) [15], and multidrug resistance protein 4 (MRP4) [16]. OCTs are a group of poly-specific transporters for subtracts typically of positively charged or zwitterions at physiological pH conditions, e.g., organic amines choline, neurotransmitters dopamine and serotonin, and vitamin B (thiamine) [17]. In one study, it was reported that long progression-free survival (PFS) in metastatic colon cancer treated with oxaliplatin is linked to high expression of OCT2 [18], implicating the role of this transporter in oxaliplatin treatment.…”
Section: The Transport Mechanisms Of Pt Drugsmentioning
confidence: 99%
“…In this Special Issue, the readers will find integrative information on transporters for organic cations. Besides reviews on physiology, pharmacology, and toxicology of these transporters [ 1 , 2 , 3 ], which offer a concise overview of the field, the readers will find original research work focusing on specific transporter aspects.…”
mentioning
confidence: 99%
“…Specifically, the review “Organic Cation Transporters in Human Physiology, Pharmacology, and Toxicology” by Samodelov et al [ 1 ] summarizes well the general aspects of physiology, pharmacology, and toxicology of transporter for organic cations. The other review “Organic Cation Transporters in the Lung—Current and Emerging (Patho)Physiological and Pharmacological Concepts” by Ali Selo et al [ 2 ] focuses on these aspects of transporters for organic cations in the lung, an important but often neglected field.…”
mentioning
confidence: 99%